Employee Work Attitudes Based On Gender in PT. DSV Solution Indonesia - Sarinah Sihombing; Tambor Harkingto Pangaribuan; Annisa Putri; Salmaa Yara Azzara (Jurnal Ilmu Multidisiplin, 2025)
This research aims to determine whether there are gender differences in work attitudes (job satisfaction, organizational commitment, turnover, and work stress). This research uses a comparative quantitative approach by comparing two independent samples, using 103 employee samples at PT DSV Solution Indonesia site Halim. The results of this research found that there were no significant differences between male and female employees at the PT DSV site Halim.